Effect of Bothrops asper (Fer-De-Lance) snake venom on erythrocyte membrane. A comparative study - Quirós, Shirley (1992)
1. The effect of Bothrops asper venom on erythrocytes of different species, sheep erythrocyte ghost vesicles and liposomes made of phospholipids from sheep erythrocytes was studied. 2. B. asper venom had a direct hemolytic effect on mouse erythrocytes, but no lytic activity on goat, rabbit, horse, toad and sheep erythrocytes. Human erythrocytes were lysed only in the presence of bovine serum albumin and Ca2+. 3. Although the phospholipase A2 activity in the venom might be involved in the lytic effect on mouse erythrocytes, there is also evidence of direct lytic factor(s) acting in the absence of calcium ions. 4. Sheep erythrocytes were modified in order to study the basis of their resistance. Enhancement of membrane fluidity and variation of pH were of no consequence for the resistance of sheep erythrocytes to the action of venom. 5. The reorganization of membranes that takes place during ghost or liposome preparation made them susceptible to B. asper venom-induced disruption. Thus the resistance of sheep erythrocytes seems related to the accessibility of the target.